Protective Effect of Curcumin Against the Toxic Effect of Acrylamide on the Rat Hippocampus - Cetin, Seda; Ozbag, Davut; Ogeturk, Murat; Dogan, Zumrut; Annac, Ebru; Dumlupinar, Ebru; Erdemli, Mehmet Erman (Springernature, 2025)
BackgroundThis study aimed to investigate the neurotoxic effects of acrylamide (AA) on the hippocampus and the potential protective effects of curcumin (CUR), a potent antioxidant, to attenuate these effects. Despite the lack of information in the literature regarding the volumetric effects of AA on the hippocampus, our study aimed to clarify this issue through stereological measurements, alongside histological and biochemical analyses.MethodsSprague-Dawley rats (similar to 250 g) were allocated into four groups: Control, AA, CUR, and AA + CUR. Both AA (50 mg/kg, intraperitoneally) and CUR (300 mg/kg, orally via gavage) were administered daily for 12 consecutive days. Following the treatment period, tissue samples were collected. Stereological, histological, and biochemical analyses were performed on the hippocampal tissue.ResultComparison of AA experimental groups data and control group data revealed that while the malondialdehyde (MDA) levels in the hippocampus increased significantly, Brain-derived neurotrophic factor (BDNF) and Glutathione (GSH) levels decreased. The results showed that CUR was effective on these levels. Histopathologically, neurons exhibited degeneration and hemorrhagic damages. According to the Cavalieri calculation, a stereological method applied to the experimental groups, no significant variation was found between the groups.ConclusionsWe determined that CUR minimizes the possible toxic effects of AA on the rat hippocampus. When the hippocampus areas were examined stereologically, we determined that it wasn't affected from this relation. We think that this was due to the short duration of our study.
Keywords: Acrylamide; Curcumin; Hippocampus; Stereology; Histopathology; Biochemistry